Analysis Of The Effect Of Location, Service Quality, And Promotion On Purchasing Decisions At Surya Utama Building Stores In Batam City: - Analya , Selvia Resti; Dabur , Feliks; Sanga , Laurensius Dihe (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This study aims to determine the effect of location, service quality, and promotion both partially and simultaneously on purchasing decisions at the Surya Utama Store Building Shop in Batam City. This research was conducted using quantitative research methods with a sample size of 100 respondents and data collection using a questionnaire. The results of this study found that the location variable (X1) tcount 1.842 < ttable r 1.985 with a significance level (0.069) > α (0.05), so location has no positive and significant effect on purchasing decisions. Service quality variable (X2) tcount 2.344> ttable 1.985 with a significance level (0.021) < α (0.05) then service quality has a positive and significant effect on purchasing decisions. Promotion variable (X3) tcount 2.349> ttable 1.985 with a significance level (0.021) < α (0.05) then promotion has a positive and significant effect on purchasing decisions. From the F test it is known that the fcount value of location, service quality, and promotion is 16.491> ftabel 2.69 with a significance level of 0.000 <0.05. This shows that the location, service quality, and promotion variables simultaneously have a positive and significant effect on purchasing decisions at the Surya Utama Store Building Shop